2014
DOI: 10.1007/s12035-014-8952-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Transformation after Tissue Plasminogen Activator Reperfusion Therapy for Ischemic Stroke: Mechanisms, Models, and Biomarkers

Abstract: Summary Intracerebral hemorrhagic transformation (HT) is well recognized as a common cause of hemorrhage in patients with ischemic stroke. HT after acute ischemic stroke contributes to early mortality and adversely affects functional recovery. The risk of HT is especially high when patients receive thrombolytic reperfusion therapy with tissue plasminogen activator, the only available treatment for ischemic stroke. Although many important publications address preclinical models of ischemic stroke, there are no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 100 publications
2
97
1
5
Order By: Relevance
“…Excessive free radicals, including hydroxyl radical, superoxide anion, and H 2 O 2 , are generated early and consume intrinsic antioxidant systems such as SOD, GSH, and GSH-px. These free radicals lead to neuronal damage by promoting lipid peroxidation, protein breakdown, and DNA damage that in turn induces cellular apoptosis, endothelial damage, and blood-brain barrier disruption [5356]. Importantly, brain is an organ with a high content of polyunsaturated fatty acids, which makes it vulnerable to free radical attacks and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive free radicals, including hydroxyl radical, superoxide anion, and H 2 O 2 , are generated early and consume intrinsic antioxidant systems such as SOD, GSH, and GSH-px. These free radicals lead to neuronal damage by promoting lipid peroxidation, protein breakdown, and DNA damage that in turn induces cellular apoptosis, endothelial damage, and blood-brain barrier disruption [5356]. Importantly, brain is an organ with a high content of polyunsaturated fatty acids, which makes it vulnerable to free radical attacks and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of MMPs (Jin et al, 2010b; Vivien et al, 2011) and PARP activity (Crome et al, 2007) have been implicated in rt-PA-mediated vascular toxicity (damaging BBB, damage to microvessels, etc.) (Jickling et al, 2014; Wang et al, 2015a; Wang et al, 2004). Further study showed that rt-PA through plasmin enhances endothelial microparticle release, which has an impact on growth and morphology of cerebral endothelial cells (Garraud et al, 2016).…”
Section: Recently Identified Therapeutic Aims and Therapiesmentioning
confidence: 99%
“…To investigate the effect of thrombin in the brain tissue, experimentally thrombin was injected into the ventricle of rats, causing vascular leakage and brain edema at 24 hours [2]. Thrombin acts on protease activated receptors, like SRC kinase, causing phosphorylation cascade on NMDA receptors [154]. and causing neuronal death via calcium dysregulation, ending up in MMP and VEGF release and a consequent BBB opening.…”
Section: Src Kinasementioning
confidence: 99%